Intellectual Capital Information and Information Asymmetry: Decision Usefulness Comparison Between the Preparers and User for IPO Issues - Kek, Wei Qi (2016)
Intellectual capital (IC) plays a crucial role in ensuring the success of businesses as a whole since it contributes to the differences between firms’ market and book values. Proper management of IC allows companies to broaden their understanding about the process of value creation and to minimise scepticism about the future progress of research and developments. To bring organisations to their full potential,academic scholars and managers have learnt to acknowledge the importance of IC. Given its role in determining companies’ value, this research study attempts to investigate the perception of preparers and users of IPO prospectus on the three categories of IC as a whole and the three categories of IC using questionnaire surveys in Malaysia. The three categories of IC are human capital (HC), internal capital (ITC) and external capital (EXC). Additionally, this study has also examined the association between IC information and share valuation as well as the relationship between firms’ characteristics and the level of underpricing. The firms’ characteristics that are examined in this study are firms’ size, profitability, leverage, growth, auditor selection and type of industry. In specifically, the perspectives of preparers and users of IPO prospectus were also examined to determine the relevance of the categories of IC information by industry. The findings suggest that preparers and users do perceive IC information to be important with EXC being the most important, followed by ITC and HC. The perceived importance of the three categories of IC information and IC as a whole were also found to have significant, positive impact on preparers’ and users’ intention to disclose and use the IC information in IPO prospectus. Looking into IC information as a whole and it respective components, results also suggest they have minimising effect on IPO underpricing and information symmetry. In contrast, among the firms’ characteristics, it was found that only firms’ size and auditor selection have a significant, positive impact on the minimising effect of IPO underpricing and information asymmetry. Also, it was deduced that the perception of the importance of IC information vary among respondents from different industries.